Experimental study on Fuel Heating of A Gas Turbine Engine - Han, Chongpeng; Zhu, Jiawei; Zhang, Xu; Xue, Yang; Diao, Qingguo; Rong, Qinfang; Zheng, Runtong; Xie, Zhenwei (Transactions on Engineering and Technology Research, 2024)
In order to mitigate the latent hazards caused by fuel retention in the gas turbine and ensure a higher ignition success rate, an investigation was conducted on the impact of fuel heating on the gas turbine. By incorporating a fuel heating device into the gas turbine, experiments were carried out to evaluate its heating performance at different positions within the fuel system. The objective was to elevate the temperature of the main fuel pipe prior to ignition, thereby reducing ignition success speed and guaranteeing successful combustion initiation. The findings revealed that placing the fuel heating device at the outlet of the fuel control device met all requirements; however, positioning it before this device failed to meet expectations. Furthermore, when subjected to heat, this particular heating device did not accurately reflect actual fuel temperature; additionally, relying solely on circulating heat within the existing fuel system proved inadequate. Consequently, based on these test results, an optimal solution involving supplementary heating devices was determined - a decision that holds immense significance for ensuring steady operation of gas turbines.